HAPPY ENDING IN JANG JIN’S ROMANCE MANHWA DEVIL NUMBER 4: READERS RESPONSE ANALYSIS - Putri, Salza Rizqiyah (ELite Journal : International Journal of Education, Language and Literature, 2025)
Readers frequently use the term "happy ending" to describe the pleasant resolution that the main characters achieve.  In the romance genre itself, happy endings are frequently linked to stories in which the protagonist finds happiness through marriage to their loving partner. Readers of romance stories frequently expect a happy ending due to the expanding concept of happy endings and their frequent usage in romance genre works. Thus, the aim of this research is to examine how readers perceive happy endings, particularly in Jang Jin's manhwa Devil Number 4. This study used a qualitative method, combining the reader response approach and Stuart Hall's concept of Encode/Decode to analyze the research. It was discovered that the author of this work emphasized that the best ending for the side characters is self-acceptance, and that happiness necessitates significant sacrifice for both the main characters and the side couple. Moreover, eight out of ten participants in this study fall into the dominant-hegemonic reader category, one into the negotiated reader category, as well as one into the oppositional reader category.  Based on this research, it can be said that the majority of Devil Number 4 readers are able to comprehend Jang Jin's message of a happy ending which is a sacrifice in order to achieve happiness.